Struktur Komunitas Serangga Dekomposer pada Tanaman Kelapa Sawit pada Fase Pertumbuhan Berbeda di PT. Mopoli Raya Rantau Aceh Tamiang - Fridayati, Diah; Nursayuti; Baihaqi; Alim, Nurmaranti; Eka Rahmi (Pangale Journal of Forestry and Environment, 2022)
Decomposer insect diversity are decomposer insect in Oil Plants in different growth phases at PT. Mopoli Raya Rantau Aceh Tamiang. This study aims to determine the high number of decomposer insect diversity in immature oil palm plantations and mature plantations at PT. Mopoli Raya. The research was carried out by the Oil Palm Plantation of PT. Mopoli Raya, Laboratory of Plant Pests and Diseases, Faculty of Agriculture Almuslim University Matangglumpangdua and Entomology Laboratory of Agriculture Gadjah Mada University Yogyakarta. The research took place from January to June 2022. The experiment used a survey method, focused on the diversity of decomposer insects. Insect sampling was carried out using a purposive sampling method, by selecting two stretches of oil palm plantations managed by the company. The observed variables were family composition and abundance of individual decomposers, composition and structure of decomposer species. The results showed that the species richness of immature oil palm was lower than that of mature plantations. This was suspected to be more intensive in immature oil palm, which resulted in a negative impact on the presence of decomposers compared to mature oil palm. The diversity of natural enemies of decomposers in producing oil palm plantations was higher, namely 67 individuals compared to immature oil palm plantations, namely 34 individuals. The benefit of research for the development of science is as a basis for pest control in company-owned and community plantations by using natural enemies found at PT. Mopoli Raya.